2020
DOI: 10.21037/tcr-20-1833
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic body radiotherapy (SBRT) for oligo-metastatic liver metastases from breast cancer, as an effective and safe alternative to surgery: a review

Abstract: The liver is a common organ of metastases from most solid malignancies, including breast cancer. LM develop in approximately 50% of all patients with metastatic breast cancer, and 5-12% of patients develop LM as the primary site of breast cancer recurrence (1-5). Breast cancer with LM (BCLM) has a poor prognosis of 4-8 months if left untreated, and 18-24 months even with systemic therapies (1,2,6). Loco-regional treatment for metastatic breast cancerSystemic hormone-and/or chemotherapy (with or without using l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Similarly, studies regarding Site-Specific Metastasis Management in OMBC were also identified and are summarised in Tables 2-4. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] These studies encompass a range of interventions, such as liver resection with 30-58% 5-year survival, diverse treatments for bone metastases showing median survival of 2-3 years and a 60-70% response rate with External Beam Radiation Therapy (EBRT), and surgical approaches for brain metastases, including combined surgery and Whole Brain Radiotherapy (WBRT) for enhanced local and distant control. 11,12,18,19,[22][23][24] Artificial Intelligence is making significant strides in BC management, with systems like LYmph Node Assistant (LYNA) achieving an AUC of 99.6% and demonstrating transformative potential in detecting metastases in sentinel lymph node biopsies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, studies regarding Site-Specific Metastasis Management in OMBC were also identified and are summarised in Tables 2-4. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] These studies encompass a range of interventions, such as liver resection with 30-58% 5-year survival, diverse treatments for bone metastases showing median survival of 2-3 years and a 60-70% response rate with External Beam Radiation Therapy (EBRT), and surgical approaches for brain metastases, including combined surgery and Whole Brain Radiotherapy (WBRT) for enhanced local and distant control. 11,12,18,19,[22][23][24] Artificial Intelligence is making significant strides in BC management, with systems like LYmph Node Assistant (LYNA) achieving an AUC of 99.6% and demonstrating transformative potential in detecting metastases in sentinel lymph node biopsies.…”
Section: Resultsmentioning
confidence: 99%
“…These patients have a poor prognosis of 4-8 months without treatment and 18-24 months even with ST. [10][11][12] Treatment options for liver metastases are mentioned in Table-2. [10][11][12][13][14][15][16][17] Bone: OMBC that spreads to the bones presents a distinct clinical profile compared to MBC originating from other primary sites, with notable differences in its clinical presentation, prognosis, and treatment strategies. 18 The advent of bisphosphonates and newer medical agents has revolutionized the initial management of bone metastases, reshaping the approach to this challenging aspect of BC care.…”
Section: Tailored Approaches To Site-specific Metastasis Management I...mentioning
confidence: 99%
“…Although surgical techniques are beyond the scope of this article, it is well established that surgery can be curative in certain clinical situations, such as pulmonary metastases from soft tissue sarcomas, osteosarcomas, and renal cell cancers, or hepatic metastases from colorectal cancer, even when multiple metastases are present. In true OMD cases, repeated surgeries and DLTs (definitive local therapies) have shown a similar likelihood of cure as the initial surgery [ 35 , 36 , 37 , 38 ]. Pulmonary and liver metastasectomies are the main surgical treatments for OMD, with notable differences in terms of technical, anatomical, and clinical-prognostic issues.…”
Section: Definitive Local Therapies In Omdmentioning
confidence: 99%
“…Local therapy with surgery or stereotactic radiation of oligometastatic disease was superior regarding overall survival, compared to systemic therapy alone [55,56]. In breast cancer, oligometastasized disease (defined as no more than five metastases) was first mentioned in 2007, and a multidisciplinary strategy including local treatment of metastasis with surgery or stereotactic radiation is recommended [53,57].…”
Section: Oligometastatic Disease In Pancreatic Cancermentioning
confidence: 99%